Caracterização físico-hídrica do solo por dados medidos e estimados com o Hydrus-1D no Cerrado e no Pantanal Mato-grossense - Pavão, Larissa Leite (2023)
The water properties of the soil surface are part of the dynamics of energy and mass exchange in the surface-atmosphere system and, therefore, the study of these properties is fundamental, in general terms, for understanding the functioning of the ecosystem. As soil water properties are directly influenced by its physical properties, it is assumed that the differences between them reflect changes in soil water fluxes. In this sense, the objective of this work is to characterize the physical water attributes of the soil through measured and estimated data in the Cerrado and Pantanal of Mato Grosso. The present work was developed in two phytophysiognomies of two distinct biomes in the state of Mato Grosso: Acurizal (Pantanal) and another in Cerradão (Cerrado). At Acurizal, soil samples were collected at 6 different points, where infiltration and hydraulic conductivity tests were also carried out. In Cerradão, a transect with 10 points, linearly spaced between them, was delimited for the collection of soil samples and conductivity data. The hydraulic conductivity tests were carried out with a DualHead infiltrometer installed in situ in two campaigns, one in 2016 in Acurizal and another in 2018 in Cerradão. The results indicated that the soils of Acurizal and Cerradão have a clayey-sandy loam texture, whereas in Acurizal there is greater porosity and lower soil density. In addition, the soil in Acurizal has good infiltration capacity, with adequate density and texture parameters, used by Hydrus-1D, to accurately predict the infiltration rate in Acurizal. Both study areas adopted good permeability and the variability of Ks is greater in the measured data than in the estimates. However, Hydrus 1D proved to be limited in estimating the Ks of the typical eutrophic haplic planosol in the Pantanal area and the dystrophic red-yellow oxisol in the Cerrado Mato-Grossense. Therefore, in addition to the content exactly, this work contributes to the direction of future studies that seek to understand, through modeling, the functioning of the physical-water processes of the soil in natural areas.